Graz 1914 : Der Volksrieg auf der Straße - Thonhofer, Bernhard (2018)
Bernhard Thonhofer researched street life in Graz at the beginning of World War I 1914 and how the Burgfrieden was shaped subsequently. By that a transformation process from a fragmented militarized society in times of peace to a society in times of war is portrayed, with its asynchrony and discrepancy, but also in its outlines. This "unity" on the streets was full of breaches and contradictions from the start. The people of Graz transformed not into a monolithic "war society" free of political, national, confessional or gender-specific conflicts. In fact the 4 years of "Volkskrieg" damaged coexistence in Graz.